The ability of Oxygen Reserve Index® to detect hyperoxia in critically ill patients - Hugues de Courson; Thomas Julien-Laferrière; Delphine Georges; Philippe Boyer; Eric Verchère; Matthieu Biais (Annals of Intensive Care, 2022)
Abstract Background Hyperoxia is associated with increased morbidity and mortality in the intensive care unit. Classical noninvasive measurements of oxygen saturation with pulse oximeters are unable to detect hyperoxia. The Oxygen Reserve Index (ORI) is a continuous noninvasive parameter provided by a multi-wave pulse oximeter that can detect hyperoxia. Primary objective was to evaluate the diagnostic accuracy of the ORI for detecting arterial oxygen tension (PaO2) > 100 mmHg in neurocritical care patients. Secondary objectives were to test the ability of ORI to detect PaO2 > 120 mmHg and the ability of pulse oximetry (SpO2) to detect PaO2 > 100 mmHg and PaO2 > 120 mmHg. Methods In this single-center study, we collected ORI and arterial blood samples every 6 h for 3 consecutive days. Diagnostic performance was estimated using the area under the receiver operating characteristic curve (AUROC). Results There were 696 simultaneous measurements of ORI and PaO2 in 62 patients. Considering the repeated measurements, the correlation between ORI and PaO2 was r = 0.13. The area under the receiver operating characteristic curve (AUROC), obtained to test the ability of ORI to detect PaO2 > 100 mmHg, was 0.567 (95% confidence interval = 0.566–0.569) with a sensitivity of 0.233 (95%CI = 0.230–0.235) and a specificity of 0.909 (95%CI = 0.907–0.910). The AUROC value obtained to test the ability of SpO2 to detect a PaO2 > 100 mmHg was 0.771 (95%CI = 0.770–0.773) with a sensitivity of 0.715 (95%CI = 0.712–0.718) and a specificity of 0.700 (95%CI = 0.697–0.703). The diagnostic performance of ORI and SpO2 for detecting PaO2 > 120 mmHg was AUROC = 0.584 (95%CI = 0.582–0.586) and 0.764 (95%CI = 0.762–0.766), respectively. The AUROC obtained for SpO2 was significantly higher than that for ORI (p < 0.01). Diagnostic performance was not affected by sedation, norepinephrine infusion, arterial partial pressure of carbon dioxide, hemoglobin level and perfusion index. Conclusion In a specific population of brain-injured patients hospitalized in a neurointensive care unit, our results suggest that the ability of ORI to diagnose hyperoxia is relatively low and that SpO2 provides better detection.